Pengembangan Kepribadian dan Karakter Sosial Peserta Didik melalui Pembiasaan di Pondok Pesantren Nurul Amal Ciamis - Kurniatin, Entin (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Personality and social character relate to good and bad human behavior. Personality and social character are the basis for knowing oneself which can help a person to control his desires, protect himself from deviant behavior and direct his life towards goodness and harmony in behavior. The phenomenon of the emergence of various personality deviations and social characters among the younger generation is a problem that must be resolved immediately because it will lead to disharmony in the life of society and the nation. Pesantren is an educational institution that can be a solution to solving moral problems that occur. The education held at the pesantren is very relevant in developing the personality and social character of students so that they become Islamic individuals. The purpose of this study was to determine the planning, implementation, and results of personality development and social character through habituation at Nurul Amal Ciamis Islamic Boarding School. This research uses a qualitative approach. Data collection techniques are carried out through interviews, observation, and documentation. The validity of the data in this study used triangulation techniques. The data analysis technique used is descriptive narrative. Data collection procedures use data reduction techniques, data presentation, and conclusions. The results of this study indicate that the planning for the development of the personality and social character of students through habituation at the Nurul Amal Islamic Boarding School through the creation of curricula, program activities, preparation of teaching human resources, and the availability of supporting infrastructure. The implementation of personality and social character development is carried out by asatidz and asatidzah with habituation through annual, semester, monthly, daily and spontaneous programs. The personalities of students that are formed are the correct faith, correct worship, morality, independence, broad insight, in good health, regular in matters, guarding time, fighting lust, and beneficial to others. Meanwhile, the social characters that are formed are social care, environmental care, tolerance, communication, and responsibility.